IMPLEMENTASI TEORI HUMANISTIK TERHADAP SIKAP DISIPLIN SHOLAT FARDHU DI MI MA’ARIF PULUTAN SALATIGA - Ustadzah Ustadzah; Fatchurrahman Fatchurrahman (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
ABSTRACTThis study aims to determine (1) The concept of humanistic theory in shaping the discipline of fardhu prayer at MI Ma'arif Pulutan; (2) Implementation of humanistic theory in shaping the discipline of fardhu prayer at MI Ma'arif Pulutan; (3) obstacles to the implementation of humanistic theory in shaping student discipline at MI Ma'arif Pulutan. this research uses qualitative methods through a descriptive approach. Researchers used several techniques in data collection, including: a) Observation (Observation) by collecting information and data related to the implementation of discipline in running fardhu prayers through humanistic theory; b) Interview (Interview) In this interview the researcher held questions and answers to people who were directly involved such as the Principal, Waka Kesiswaan and also teachers who assisted students of MI Ma'arif Pulutan; c) Documentation: The documentation method researchers use in obtaining data about student discipline in carrying out fard prayers at MI Ma'arif Pulutan. Researchers use Triangulation, collaboration of methods, namely observation, interviews and documentation that can reinforce each other. The results of this study indicate that (1) The concept of humanisitk learning theory is defined as maximizing the process of development in physical and spiritual activities. first physiological or biological needs. Second, the need for security. Third, the need for love and belonging. Fourth, the need for self-esteem. Fifth, the need for self-actualization or personal development; (2) The initial step in the implementation of student discipline in carrying out this fardhu prayer by making an agreement involving school residents, sharing questions with students, showing visually appealing videos; (3) The obstacles to the implementation of humanistic theory in MI Ma'arif Pulutan are low motivation, poor time management, inconsistent educators in providing reinforcement, students who do not yet have awareness of the importance of discipline.